Evaluating the effect of the compressed air wheel cleaning in grinding the AISI 4340 steel with CBN and MQL with water - Bianchi, Eduardo Carlos [UNESP]; Sato, Bruno Kenta [UNESP]; Sales, Alan Rodrigo [UNESP]; Lopes, Jose Claudio [UNESP]; Mello, Hamilton Jose de [UNESP]; Angelo Sanchez, Luiz Eduardo de [UNESP]; Diniz, Anselmo Eduardo; Aguiar, Paulo Roberto [UNESP] (Springer, 2018)
The application of minimum quantity of lubricant (MQL) in grinding process is a challenging task. Once the MQL is considered an environmentally friendly technique, its implementation in grinding process is interesting to achieve cleaner production. On the other hand, its use brings some problems to the process, such as intensification of grinding wheel clogging phenomenon and increase of cutting temperatures, which impairs on the attainment of a good surface quality, together with dimensional and geometrical accuracy. Looking for improving the MQL efficiency in grinding process, two eco-friendly techniques were found: the addition of water in the MQL and the wheel cleaning system with compressed air. The present research seeks to evaluate the improvement of MQL application in grinding using the combination of these techniques. Both techniques MQL + water and wheel cleaning system are innovative, since there are almost no articles in literature citing its use. The experiments were performed in an external cylindrical plunge grinding using a vitrified cubic boron nitrite (CBN) grinding wheel. The workpiece material was a quenched and tempered AISI 4340 steel. The cooling methods employed in the process were a conventional method (flood coolant), MQL + water (1:1, 1:3, 1:5 part of oil per parts of water), MQL + water + cleaning system (1:1, 1:3, 1:5 part of oil per parts of water), and MQL with and without cleaning system. Results were analyzed based on some workpiece parameters (roughness, roundness deviation, and microstructure) and on diametrical wheel wear and grinding power. The addition of water allied to cleaning system with compressed air provided the best results among those using the MQL technique, with results comparable to the conventional cooling method.
Keywords: Cylindrical external plunge grinding; Minimum quantity of lubricant with water; Compressed air wheel cleaning